CD160 Plays a Protective Role During Chronic Infection by Enhancing Both Functionalities and Proliferative Capacity of CD8+ T Cells - Zhang, Linxia; Zhang, Anli; Xu, Jun; Qiu, Chao; Zhu, Lingyan; Qiu, Chenli; Fu, Weihui; Wang, Ying; Ye, Lilin; Fu, Yang-xin; Zhao, Chen; Zhang, Xiaoyan; et al. (Frontiers in Immunology, 2020)
The understanding of protective immunity during HIV infection remains elusive. Here we showed that CD160 defines a polyfunctional and proliferative CD8+ T cell subset with a protective role during chronic HIV-1 infection. CD160+ CD8+ T cells derived from HIV+ patients correlated with slow progressions both in a cross-sectional study and in a 60-month longitudinal cohort, displaying enhanced cytotoxicity and proliferative capacity in response to HIV Gag stimulation; triggering CD160 promoted their functionalities through MEK–ERK and PI3K–AKT pathways. These observations were corroborated by studying chronic lymphocytic choriomeningitis virus (LCMV) infection in mice. The genetic ablation of CD160 severely impaired LCMV-specific CD8+ T cell functionalities and thereby resulted in loss of virus control. Interestingly, transcriptional profiling showed multiple costimulatory and survival pathways likely to be involved in CD160+ T cell development. Our data demonstrated that CD160 acts as a costimulatory molecule positively regulating CD8+ T cells during chronic viral infections, thus representing a potential target for immune intervention.